The Role of Bacterial Protease Enzymes and In Silico Prediction on the Effectiveness of Medical Applications - Muliawan, Adi; Ananta, Yorasakhi; Fitri, Salsabila Dwi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
Bacterial protease enzymes have a wide range of medical applications, particularly in the treatment of infected wounds and therapy for protein digestion disorders. Proteases produced by bacteria such as Bacillus pseudomycoides show great potential for medical therapy due to their ability to break down proteins in the human body. In silico prediction using bioinformatics software such as AutoDock and PyMOL allows researchers to analyze the three-dimensional structure and molecular interactions of proteases with target substrates before conducting laboratory experiments. This article examines the role of bacterial protease enzymes in medical applications and the benefits of using in silico prediction to study the therapeutic potential of proteases. With a combined approach of experimentation and in silico analysis, the process of developing protease-based therapies can be more efficient and faster. This study emphasizes the importance of bioinformatics approaches in accelerating the discovery of enzyme-based medical therapies for future clinical applications.